An Exploration of Cross-Cultural and Transtemporal Translation Strategies Employed in the Chinese-to-English Translation of Selected Chapters From Huangdi Neijing·Su Wen - Tang, Lin (Auckland University of Technology, 2026)
Traditional Chinese Medicine (TCM) is increasingly explored and valued in biomedical, technological and policy domains internationally, including in China and in English-speaking countries such as New Zealand, Australia, the United Kingdom, and more. Given this growing interest among healthcare researchers and the wider public, the present study aimed to explore the Chinese to English translations of two TCM texts since the cultural underpinnings and original philosophy present serious cross-cultural and transtemporal challenges. This research set out to explore the translation strategies employed in two selected chapters of the Huangdi Neijing·Su Wen from Chinese to English, focusing on the challenges posed by cross-cultural and transtemporal contexts. Using a multi-methodological qualitative approach, the research integrated a study-specific taxonomy for comparative analysis, expert validation via a Delphi-style method with an expert panel of professional translators, and a reception study with English-speaking TCM users in Auckland, New Zealand. Data were analysed using Braun and Clarke’s (2006) thematic analysis approach. The findings reveal that discourse-level coherence depends on the consistent rendering of recurring terms; conversely, lexical variation weakens conceptual links and interrupts the reasoning chain. The research found that plain English at times recasts TCM concepts as biomedical or general wellness frameworks, causing a "frame shift" that weakens original nuances. Furthermore, the translator's voice and register were found to shape authority as much as lexical accuracy. Professional translator participants prioritised hybrid solutions that balance conceptual integrity with readability, emphasising that consistency outweighs sentence-level fluency. Meantime, end-users prioritised "making sense" and viewed natural English as a marker of trust, though they cautioned against meaning drift. They favoured pinyin with brief in-text glosses for clarity but cautioned against excessive reading loads, while also accepting unfamiliar English vocabulary as long as it remained consistent and briefly explained. This research therefore contributes an evidence-based account of how cross-cultural and transtemporal challenges jointly shape TCM translation. It proposes a practical taxonomy for evaluating translations involving both cultural and temporal distance, serving insights for producing accessible, trustworthy translations for learners and consumers in everyday health contexts.